2021
DOI: 10.1007/978-3-030-72582-2_26
|View full text |Cite
|
Sign up to set email alerts
|

Can Encrypted DNS Be Fast?

Abstract: In this paper, we study the performance of encrypted DNS protocols and conventional DNS from thousands of home networks in the United States, over one month in 2020. We perform these measurements from the homes of 2,693 participating panelists in the Federal Communications Commission’s (FCC) Measuring Broadband America program. We found that clients do not have to trade DNS performance for privacy. For certain resolvers, DoT was able to perform faster than DNS in median response times, even as latency increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…From the above studies, it is quite clear that DNS encryption protocols perform not so well when network conditions are less ideal. This remark has also been drawn from measurement research works done on edge networks [38,46,57,81] (e.g., home) that have substantial distance from the essential Internet infrastructures. By measuring DoH resolution times from 22K unique hosts across the world, the authors of [38] found that hosts in high-income countries/regions with better Internet infrastructure are less likely to have performance degradation.…”
Section: Performance Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…From the above studies, it is quite clear that DNS encryption protocols perform not so well when network conditions are less ideal. This remark has also been drawn from measurement research works done on edge networks [38,46,57,81] (e.g., home) that have substantial distance from the essential Internet infrastructures. By measuring DoH resolution times from 22K unique hosts across the world, the authors of [38] found that hosts in high-income countries/regions with better Internet infrastructure are less likely to have performance degradation.…”
Section: Performance Analysismentioning
confidence: 95%
“…The authors of [46] measured DoT lookups from 3.2K RIPE Atlas probes deployed in home networks and obtained high failure rates (up to 32%) and equivalent response times (around 150ms) compared with plaintext DNS, which had its low failure rates of less than 3%. Lastly, A. Hounsel et al [57] performed measurements on more than 2500 home networks participating in a Measuring Broadband America program by the Federal Communications Commission (FCC). They highlighted that DNS clients could periodically conduct active probing in order to select their optimal user settings in terms of the choice of protocol (DoT or DoH)…”
Section: Performance Analysismentioning
confidence: 99%
“…However, when DoH connection is reused for multiple queries, the additional latency is negligible. Another study performed by Hounsel et al [12] shows that DoH latency and reliability strongly depend on the selected resolver. This is also supported by Jerabek et al [13] who studied DoH resolver behavior and the distribution of DoH packet sizes depending on used resolvers.…”
Section: Related Research On Dohmentioning
confidence: 96%
“…An example of such usage is the PsiXbot malware. The analysis12 www.virustotal.com created by the Proofpoint threat insight team [57] reveals that PsiXbot uses the hardcoded dns.google.com resolver and issues a JSON-based DoH request via HTTP 1.1 to resolve a hardcoded C2 domain.…”
mentioning
confidence: 99%
“…This problem was originally addressed by the encrypted protocols DNS over TLS (DoT) [24] and DNS over HTTPS (DoH) [21], which have been integrated by browsers and public DNS resolvers since 2016 [9,12,16,17]. As these protocols have been extensively studied in terms of response times [5,8,23,40,40,53] and impact on Web performance [4,5,22], it has become clear that both DoT and DoH are constrained by the round-trips required for the handshakes of the underlying transport (TCP) and encryption (TLS) protocols.…”
Section: Introductionmentioning
confidence: 99%